Understanding the Positive Announcement Effects of Private Equity Placements: New Insights from Hong Kong Data - Wu, Xueping; Wang, Zheng; Yao, Jun (Review of Finance, 2005)
Abstract The literature has documented positive announcement effects for privately placed seasoned equity issues.This study shows positive announcement effects not only for private but also for public placements in Hong Kong. Our unique data offer new insights not obtainable from U.S. data as we examine the cross-sections of the announcement effects. Most importantly, we find that the announcement effect is more likely to be positive for smaller issuers, such as private placing firms and some public issuers where asymmetric information arises more from growth than from assets in place. This finding is consistent with the generalized Myers-Majluf model.